On the volume from planar sections through a curve - Gual-Arnau, Ximo (Image analysis and stereology, 2005)
We derive a formula to obtain the volume of a compact domain from planar sections through a curve. From this formula we propose a stereological estimator for the volume which generalizes some known unbiased estimators which use a systematic sampling scheme. Moreover we formulate a Cavalieri's principle for compact domains is spaces of constant curvature gama.
Keywords: Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; volumen; prerezi; stereologija